Quality and cost characteristics of tourist (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The tourism services provided in the hotel organizations are a set of material and moral elements that represent tourist attractions that are offered to the guests in order to satisfy their needs and desires are accommodation, food, drink and other facilities to reach the satisfaction and satisfaction of guests.Where these tourist services need a mechanism to ensure their quality by working to identify and calculate the costs of these services properly and accurately with the attempt to referendum and reduce the waste and loss to reduce these costs while providing the finest types of tourism services by calculating the cost of production and the administration seeks to reduce Non-essential activities through hotel activities that add value and where the guest is willing to pay and this activity cannot be canceled because it affects the quality of tourist services.The second axis tackled the concepts of quality costs, levels, types and methods of determining them. The third axis dealt with the relationship between quality control and cost reduction. The fourth axis dealt with the characteristics of the quality, Tourism services, and in the fifth poplar was presented the most important conclusions and recommendations reached by the researchers